2022
DOI: 10.3389/fpsyg.2022.1032675
|View full text |Cite
|
Sign up to set email alerts
|

English-learning stress and performance in Chinese college students: A serial mediation model of academic anxiety and academic burnout and the protective effect of grit

Abstract: IntroductionHaving to adapt to a new environment with various other challenges while completing their studies, Chinese college students experience intense stress related to the study of the English language. However, there has been little research on the serial mediating mechanism of English-learning stress on English academic performance.MethodsPresent study recruited 1130 undergraduate students to finish self-report online questionnaire to collect the information about their English-learning stress, academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“… 3 If adolescents face more burden and stress in the long term, it will lead to numerous problems such as learning burnout. 4 Learning burnout has been shown to be a risk factor for depression, school dropout and self-harm. 5 Another important problem resulting from the “double reduction” policy was that, under the condition of relatively reduced learning time, some students were addicted to watching short videos, playing games, chatting and other recreational activities on smart phones which occupy most of their leisure time.…”
Section: Introductionmentioning
confidence: 99%
“… 3 If adolescents face more burden and stress in the long term, it will lead to numerous problems such as learning burnout. 4 Learning burnout has been shown to be a risk factor for depression, school dropout and self-harm. 5 Another important problem resulting from the “double reduction” policy was that, under the condition of relatively reduced learning time, some students were addicted to watching short videos, playing games, chatting and other recreational activities on smart phones which occupy most of their leisure time.…”
Section: Introductionmentioning
confidence: 99%
“…A study in the UK reported that depression predicted a decline in examination performance [ 40 ]. Moreover, studies aimed at undergraduate students supports that academic stress is an impediment to academic performance, [ 41 43 ] although there were few study focused on the association between academic stress with academic performance in adolescents. A moderate level of academic stress helps to increase academic self-efficacy and obtain better educational outcomes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A moderate level of academic stress helps to increase academic self-efficacy and obtain better educational outcomes [ 42 ]. However, once students experienced high stress levels beyond their load-bearing potential, it could result in school burnout and worse performance [ 43 ]. Regarding externalizing behaviors (physical fight and bullying), several studies are consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al discovered that a considerable percentage of returned migrant children had declining attitudes toward learning, more learning pressure, and worse academic and mental health performance than non-returned migrant children in a study of 17,924 4th to 5th-grade students in China [12]. Longterm academic issues, such as academic stress, anxiety, and subpar performance, cause LB in students, as demonstrated by a study conducted by Xu et al on 1,130 undergraduate students in a southern Chinese city [21]. The conservation theory and the loss spiral effect of the resource conservation model state that people will deplete resources when they are trying to cope with stress.…”
Section: The Relationship Between Lb and Ebp In Returned Middle Schoo...mentioning
confidence: 99%